Prevalence and determinants of instrumental activities of daily living (IADL) disability among community dwelling elderly in a semi-urban setting in Peninsular Malaysia - Murat, Muhammad Faizal; Ibrahim, Zuriati; Adznam, Siti Nur ‘Asyura; Chan, Yoke Mun (Nutrition Society of Malaysia, 2019)
Introduction: The ability to perform daily living activities among the elderly is important, as physical disability may lead to dependency and various public health implications. This study aimed to determine the prevalence of instrumental activities of daily living (IADL) disability and its association with socio-demographic characteristics, dietary intake, social participation, perceived-health-status and risk of falls. Methods: This cross-sectional study was conducted among community based elderly in the Gombak District of Selangor. 258 respondents aged 60-88 years old (mean age 66±6.5 years) were recruited through multi-stage proportional sampling. Most of the respondents (88.4%) aged 60-74 years and 11.6% were ≥75 years. IADL disability was determined using an eight-item IADL scale. The presence of IADL disability was defined as needing help in at least one or more of eight-IADL activities. Dietary intake and fall risk were assessed using diet history questionnaire (DHQ) and 21-item fall risk index (FRI-21), respectively. Results: The prevalence of IADL disability among the respondents was 58.1%. A binary logistic regression analyses showed that the following factors predicted IADL disability: advanced age (≥75 years, OR=6.4; 95% CI: 1.3, 30.8), being unmarried (OR=2.5; 95% CI: 1.1, 5.9), unemployed/retired (OR=2.3; 95% CI: 1.2, 4.3), and at risk of falls (OR=2.5; 95% CI: 1.3, 6.1). Conclusion: Predictors such as marriage and employment highlight the importance of social support among elderly. In practical terms, this means that it is incumbent upon caregivers, family members, and the community to provide both physical and emotional support if the functional status of the elderly is to be improved.